Revising Computerized Therapy for Wider Appeal Among Adolescents: Youth Perspectives on a Revised Version of SPARX - Fleming, Theresa M.; Stasiak, Karolina; Moselen, Emma; Hermansson-Webb, Eve; Shepherd, Matthew; Lucassen, Mathijs; Bavin, Lynda M.; Merry, Sally Nicola (Frontiers in Psychiatry, 2019)
Background: The way in which computerized therapy is presented may be important for its uptake. We aimed to explore adolescents’ views on the appeal of a tested computerized cognitive behavioral therapy (CCBT) for depression (SPARX), and a revised version (SPARX-R). The versions were similar but while SPARX is presented explicitly as a treatment for depression, SPARX-R is presented as providing skills that could be useful for young people for when they were depressed, down, angry or stressed. Methods: We held nine focus groups with a total of 79 adolescents (13–19 years old; 47 females; 34 New Zealand European; 22 Māori or Pacific; 60 reported having experienced feeling down or low for at least several days in a row). Groups viewed the opening sequences of SPARX and SPARX-R (in random order), then took part in a semi-structured discussion and completed a brief questionnaire. Responses were analyzed using a general inductive approach. Results: Participants considered both SPARX and SPARX-R useful and considered the stated purpose of the program to be important. Four themes contrasted the two approaches: the first, ‘naming depression is risky’, referred to perceptions that an explicit focus on depression could be off-putting, including for adolescents with depression. The second theme of ‘universality’ reflected preferences for a universal approach as young people might not recognize that they were depressed, and that all would benefit from the program. In contrast, ‘validation’ reflected the view of a significant minority that naming depression could be validating for some. Finally, the theme of ‘choice’ reflected a near-unanimously expressed preference for both options to be offered, allowing user choice. In questionnaire responses, 40 (68%) of participants preferred SPARX-R, 13 (18%) preferred SPARX, whilst 10 (14%) ‘didn’t mind’. Responses were similar among participants who reported that they had experienced at least a few days of low mood and those who had not. Conclusions: The way a CCBT program is presented may have implications for its appeal. The potential population impact of CCBT programs explicitly targeting depression and those targeting more universal feelings such as being stressed or depressed should be explored for varied user groups.